2005
DOI: 10.1086/432730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV‐1 Serostatus, HIV‐1 RNA Concentration, and CD4 Cell Count on the Incidence of Malaria Infection in a Cohort of Adults in Rural Malawi

Abstract: HIV-infected adults in malaria-endemic areas are at increased risk for malaria. Where possible, additional malaria prevention efforts should be targeted at this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
97
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 19 publications
8
97
3
Order By: Relevance
“…Areas of malaria and HIV endemicity share a wide geographic overlap, putting millions of people at risk of co-infection and consequently at risk for more severe clinical disease [2][3][4][5][6][7][8][9][10] . The two diseases negatively interact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of malaria and HIV endemicity share a wide geographic overlap, putting millions of people at risk of co-infection and consequently at risk for more severe clinical disease [2][3][4][5][6][7][8][9][10] . The two diseases negatively interact.…”
Section: Introductionmentioning
confidence: 99%
“…The two diseases negatively interact. In HIV-infected individuals, higher HIV viral loads and temporary decreases in CD4 + T-cell counts can be seen during a malaria infection, while malaria parasite burdens and risk of clinical and severe malaria are higher in co-infected individuals 2,3,5,7,8,10 . The mechanisms by which HIV increases malaria severity are not fully understood and warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence abound indicating that HIV infection interacts negatively with malaria, with each disease driving the progression and transmission of the other (Whitworth et al, 2000;French et al, 2001;Patnaik et al, 2005). Some studies have demonstrated that HIV increases the risk of clinical and severe malaria, while malaria increases HIV replication in vitro and in vivo (Xiao et al, 1998;Whitworth et al, 2000;French et al, 2001;Patnaik et al, 2005;Kamya et al, 2006). Both HIV infection and malaria are known to critically intersect in pregnancy and have serious consequences in pregnant women, their foetuses and their infants (Ticconi et al, 2003;ter Kuile et al, 2004).…”
Section: Effect Of Maternal Hiv Infection On Congenital Malariamentioning
confidence: 99%
“…1 In areas where malaria transmission is stable, HIV infection has been found to approximately double the risk of malaria parasitemia and clinical malaria in nonpregnant women. 2 Also, HIV infection is associated with an increased prevalence [2][3][4][5] and density 6 of parasitemia and an increased prevalence of clinical malaria 2,3,[7][8][9] particularly in patients with severe immunosuppression. 2,3,7,[10][11][12] In a cohort study in Uganda, the risk of clinical malaria was increased three times in patients with CD4 cell counts of 200-499 cells/μL and increased six times in patients with counts 200 cells/μL than in patients with counts 500 cells/μL; parasitemia also increased as the CD4 cell count decreased.…”
Section: Introductionmentioning
confidence: 99%
“…2 Also, HIV infection is associated with an increased prevalence [2][3][4][5] and density 6 of parasitemia and an increased prevalence of clinical malaria 2,3,[7][8][9] particularly in patients with severe immunosuppression. 2,3,7,[10][11][12] In a cohort study in Uganda, the risk of clinical malaria was increased three times in patients with CD4 cell counts of 200-499 cells/μL and increased six times in patients with counts 200 cells/μL than in patients with counts 500 cells/μL; parasitemia also increased as the CD4 cell count decreased. 2 The prevalence of severe malaria and mortality in areas of stable transmission was not affected by HIV infection in previous studies, [13][14][15][16] but data from three recent studies challenge this finding.…”
Section: Introductionmentioning
confidence: 99%